Palestine is throwing a party and the whole world is invited : capital and state building in the West Bank - Rabie, Kareem, 1980- (Duke University Press, 2021)
"Kareem Rabie examines how Palestine's desire to fully integrate its economy into global markets through large-scale investment projects represented a shift away from political state building with the hope that a thriving economy would lead to a free and functioning Palestinian state."--